Women’s investment club integrates climate-risk into accelerator and contributes to the uptake of climate-smart solutions in Senegal. AICCRA’s research and engagement is enhancing the awareness and capacity for private actors - Derenoncourt, Marie Ena (2023)
Women's Investment Club incorporates climate risks analysis in their business support program and bring sustainability and climate adaptation in the financing process of women-led enterprises. Through the Gender-Smart Accelerator program, 20 women-led value chain enterprises supported by AICCRA and WIC are developing investable CSA business models. Inspired its engagement with AICCRA, WIC organized a panel discussion on Green Finance during the Women Investment Forum, to create awareness about climate risk and inform the 300 participants about AICCRA’s tools and innovations